2019
DOI: 10.3390/ijms20225634
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MicroRNAs That Respond to Soybean Cyst Nematode Infection in Early Stages in Resistant and Susceptible Soybean Cultivars

Abstract: Soybean cyst nematode (SCN) causes heavy losses to soybean yield. In order to investigate the roles of soybean miRNAs during the early stages of infection (1 and 5 dpi), 24 small RNA libraries were constructed from SCN resistant cultivar Huipizhi (HPZ) and the susceptible Williams 82 (W82) cultivar for high-throughput sequencing. By sequencing the small RNA libraries, a total of 634 known miRNAs were identified, and 252 novel miRNAs were predicted. Altogether, 14 known miRNAs belonging to 13 families, and 26 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Our previous study also found several conserved plant miRNAs differently expressed at the early stage of SCN infection in soybean roots, including miR159. Other studies also found that miR159 was significantly downregulated in different soybean cultivars at different SCN infection stages [ 10 , 11 , 33 , 34 ]. These results suggested that miR159 family members may respond to SCN differently.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Our previous study also found several conserved plant miRNAs differently expressed at the early stage of SCN infection in soybean roots, including miR159. Other studies also found that miR159 was significantly downregulated in different soybean cultivars at different SCN infection stages [ 10 , 11 , 33 , 34 ]. These results suggested that miR159 family members may respond to SCN differently.…”
Section: Discussionmentioning
confidence: 80%
“…Several previous studies have found soybean miR159 family members differently expressed during SCN parasitism [ 10 , 11 , 33 , 34 ]. The evidence from high-throughput sequencing implicated that the soybean miR159- GAMYB module may play an important role in soybean resistance to SCN.…”
Section: Introductionmentioning
confidence: 99%
“…H. glycines' survival depends on the development and maintenance of the syncytium. Under nematode stress conditions, resistant soybean cultivars confine the arrangement and advancement of syncytia through several mechanisms during the early phases of soybean-SCN interactions [49][50][51][52][53][54][55][56]. Nevertheless, the scopoletin-coating effect on suppressing the development of syncytia in susceptible soybean cultivars has been unclear.…”
Section: Discussionmentioning
confidence: 99%
“…For observing histological alterations in TJ2 and CKJ2 at 9 dpi, root samples were cut in 1-cm cubes prior to fixation with Carnoy's fix solution for measuring the syncytia, according to the method described by Lei, P [55].…”
Section: Histological Observationmentioning
confidence: 99%
“…However, these studies mostly focus on the ability to uptake double strand RNAs (dsRNAs) from the environment (Huang et al, 2006;Tian et al, 2019) rather than on the cross-kingdom transfer of plant miRNAs. Many studies have investigated the involvement of plant miRNAs and their corresponded gene targets in response to phytonematodes infection (Hewezi et al, 2008;Li et al, 2012;Lei et al, 2019;Pan et al, 2019). Transcriptomic analyses evidenced extensive reprogramming of gene expression at the nematode feeding sites, modulated by plant miRNAs; also, some conserved miRNAs were shown to have analogous roles in feeding site formation in different plant species (Jaubert-Possamai et al, 2019).…”
Section: Plant-parasite Mirnas Cross-kingdom Transfer: Alternative Tomentioning
confidence: 99%